Strategi Pengembangan Produk Unggulan Daerah pada Usaha Tempe dengan Metode SWOT dan QSPM - Hatta, Mochammad; Tjahjani, Ida Kusnawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Tempeh is a typical Indonesian food that is rich in benefits, affordable, and accepted internationally. The objectives of this research are: 1). Identify various internal and external factors that influence the development of the tempe business and propose development strategies to maintain its sustainability. Using the Fishbone Diagram to identify and analyze the causes of a factor, followed by applying 2 analytical methods, namely: 1). SWOT analysis, and 2). QSPM analysis. The research results show that based on the IE Analysis and SWOT Analysis, the position of the Sumber Makmur tempeh business is in quadrant I, which means that the business can seize existing opportunities by making maximum use of its strengths. The strategy that must be implemented now is to support aggressive growth policies (Growth Oriented Strategy). In the QSPM Analysis, the highest TAS results are found in alternative quality improvement strategies at low and affordable prices in order to meet high needs and gain public recognition